NHANES-based analysis of the correlation between leisure-time physical activity, serum cotinine levels and periodontitis risk - Hua Fu; Diya Zhang; Yining Li (BMC, 2024)
Abstract Objective To investigate the association of leisure-time physical activity and serum cotinine levels with the risk of periodontitis in the general population and to further analyze the interaction between leisure-time physical activity and serum cotinine levels on the risk of periodontitis. Methods This was a cross-sectional study, extracting data from 9605 (56.19%) participants in the National Health and Nutrition Examination Survey (NHANES) database from 2009 to 2014, and analyzing the relationship and interaction effects of serum cotinine level, leisure time physical activity, and risk of periodontitis by weighted univariate logistic modeling; Effect sizes were determined using ratio of ratios (OR), 95% confidence intervals (95% CI). Results 5,397 (56.19%) of 9,605 participants had periodontitis; an increased risk of periodontitis was found in those in the leisure time physical activity intensity < 750 MET × min/week group (OR = 1.44, 95% CI: 1.17-1.78). Serum cotinine levels ≥ 0.05 ng/ml were associated with an increased risk of periodontitis (OR = 1.99, 95% CI: 1.69-2.33). The group with low leisure physical activity and serum cotinine levels ≥ 0.05 ng/ml had an increased risk of periodontitis compared to the group with high leisure physical activity and serum cotinine levels < 0.05 ng/ml (OR = 2.48, 95% CI: 1.88-3.27). Interaction metrics RERI = 0.90 (95% CI: 0.44-1.36) and API = 0.36 (95% CI: 0.18-0.55); CI for SI = 2.55 (95% CI: 1.03-6.28). for API 0.36. Conclusion Leisure time physical activity intensity interacted with smoking exposure on periodontitis risk and may provide the general population with the opportunity to Increasing leisure-time physical activity and smoking cessation may provide recommendations for the general population.